2022
DOI: 10.1016/j.cllc.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes for Plasma-Based Comprehensive Genomic Profiling Versus Standard-of-Care Tissue Testing in Advanced Non–Small Cell Lung Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Previous studies have shown similar shorter turnaround times with liquid compared to tissue-based biopsy in NSCLC and shorter time to treatment. These studies include the Canadian VALUE study where the mean turnaround time ( ± SD) was 7.7 ± 1.6 vs. 20.8 ± 9.8 days for liquid vs. tissue-based biopsy, as well as the North American NILE study involving 282 patients with advanced lung adenocarcinoma where the time to treatment was significantly shorter with liquid biopsy compared to tumor tissue molecular profiling (median 18 vs. 31 days, respectively, p = 0.0008) ( 18 , 19 ). Our study is also consistent with the VALUE study with respect to the high concordance rate between the liquid and solid biopsy results ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown similar shorter turnaround times with liquid compared to tissue-based biopsy in NSCLC and shorter time to treatment. These studies include the Canadian VALUE study where the mean turnaround time ( ± SD) was 7.7 ± 1.6 vs. 20.8 ± 9.8 days for liquid vs. tissue-based biopsy, as well as the North American NILE study involving 282 patients with advanced lung adenocarcinoma where the time to treatment was significantly shorter with liquid biopsy compared to tumor tissue molecular profiling (median 18 vs. 31 days, respectively, p = 0.0008) ( 18 , 19 ). Our study is also consistent with the VALUE study with respect to the high concordance rate between the liquid and solid biopsy results ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Guardant 360 TM platform is a US FDA-approved, 73-gene next-generation sequencing (NGS) test that detects plasma ctDNA fragments along with germline and other somatic cell-free DNA (cfDNA). 18 A limitation of the Guardant 360 TM platform is its decreased sensitivity to detect ctDNA in mucinous tumors. 19 ctDNA analysis was performed on blood samples collected either pretreatment (chemotherapy, radiation, or surgery) or early treatment (within 1 month of the initiation of treatment).…”
Section: Methodsmentioning
confidence: 99%
“…Limited but significant studies on ctDNA analysis have shown some important results regarding the detection of ROS1 rearrangements in plasma as a tissue surrogate. Most of the studies included NGS panels for the most important therapeutically targetable mutations for the appropriate TKI therapy in NSCLC patients or treatment monitoring [ 215 , 216 , 217 ] and also proved the clinical utility of cfDNA testing at diagnosis and the potential it offers for faster, minimally invasive therapeutic decisions [ 218 ]…”
Section: Liquid Biopsy Testing In Nsclcmentioning
confidence: 99%